Exploring Organizational Democracy from the Perspective of Public Managers: A Phenomenological Approach - Bahari, Ehsan; Ahmadi, Kumars; Salavati , Adel (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2024)
Objective: This study aims to explore the experiences and perceptions of public managers in Iranian governmental organizations regarding organizational democracy. By adopting a phenomenological approach, the research seeks to understand the essence of organizational democracy from the perspective of those who have experienced it firsthand, highlighting the key themes and subthemes that emerge from their lived experiences. Methodology: The study employs a qualitative research design with a phenomenological approach to capture the lived experiences of public managers. A non-random snowball sampling method was used to select 15 public managers from various governmental organizations in Iran. Data were collected through semi-structured interviews, and the analysis continued until theoretical saturation was reached. The interviews were transcribed verbatim and analyzed using thematic analysis to identify key themes and subthemes. Findings: Four major themes emerged from the data: transparent and accountable management, independent organizations, personal fulfillment, and free and fair participation. Subthemes included the transition to democratic supervision, planning for civic participation, financial support for employees, fostering innovation, and integrating diverse values. The findings reveal a significant shift towards more democratic organizational practices, emphasizing transparency, employee empowerment, and participatory decision-making processes. Conclusion: The study highlights the critical role of transparency, participatory decision-making, and employee empowerment in enhancing organizational effectiveness and employee satisfaction within Iranian governmental organizations. .